DESENVOLVIMENTO E CARACTERIZAÇÃO DE SUSPENSÕES CONTENDO NANOCÁPSULAS DE ADAPALENO COM DIFERENTES NÚCLEOS OLEOSOS - Barrios, Jerusa Goi (2010)
Acne is one of the most common inflammatory conditions affecting the skin. There are several drugs to treat it, but despite the benefits of these treatments in their free form, there are common side effects to them, especially when applied topically. Among these drugs is the adapalene with comedolitic action and effects on the abnormal process of keratinization and epidermal differentiation, phenomena present in acne vulgaris. This study aimed to prepare polymer nanocapsules of adapalene through the method of interfacial deposition of preformed polymer using different oil cores (tea tree oil and Miglyol®). The suspensions were characterized by determining the pH, particle diameter, polidispersion rate, zeta potential, association rate and dosage of the drug. The stability was determined at different temperatures and under light UVA. In vitro release studies and analysis of mathematical modeling of kinetic release profiles were carried out by comparing suspensions containing adapalene polymer nanocapsules and nanodispersions and without the presence of the polymer. The formulations were stored at room temperature (25 ° C), refrigerator (-4 ° C) and oven (40 ° C) for 3 months and analyzed at 0, 7, 15, 30, 60 and 90 days after preparation. Both suspensions containing Miglyol® polymer nanocapsules (NC-AD-Miglyol®) as the tea tree oil polymer nanocapsules (NC-AD-tea tree oil) showed acidic pH, particle diameter below 300 nm and zeta potential negative. The rate of association of adapalene in the NC-AD-tea tree oil was 95.4% while the NC-AD-Miglyol® was 84.1%. The dosage of the drug showed that the NCAD- tea tree oil exerts a greater stabilizing effect than the other formulations. The shelf life estimated for the NC-AD-tea tree oil was higher when compared to nanodispersion (ND) and NC-AD-Miglyol®. Mathematical modeling showed that the ND and NC-AD-Miglyol® followed a kinetic profile, according to the mono-exponential model with half-lives of 3.53 and 8.43 hours. On the other hand, NC-AD-tea tree oil suspension followed a bi-exponential, model with half-lives of 4.07 hours for the fast phase and 230.6 hours for the sustained phase. Therefore, we can say that the adapalene formulation NC-AD-Miglyol® locates largely more externally in the polymer nanocapsule, while in the NC-AD-tea tree oil, it is dissolved in the oil core of the polymer nanocapsule, suggesting a sustained release. We evaluated the photostability of adapalene nanocoated with Miglyol® oil and tea tree oil under UVA irradiation, and concluded that the nanoencapsulation with tea tree oil increases the stability of the active, offering increased protection it from degradation. In analysis by multiple scattering of light, the suspensions showed a tendency of sedimentation, but the NC-ADMiglyol ® proved to be more likely to destabilization. The validation of the method was satisfactory for all parameters analyzed. Though the results obtained, it can be concluded that the suspension containing NC-AD-tea tree oil showed better physical and chemical characteristics and stability, representing best technological feasibility fot the pharmaceutical area.